1998
DOI: 10.1046/j.1365-313x.1998.00220.x
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic oxidations in the biosynthesis of complex alkaloids

Abstract: SummaryThe biosynthesis of complex alkaloids in plants involves enzymes that, due to high substrate specificity, appear to have evolved solely for a role in secondary metabolism. At least one class of these enzymes, the oxidoreductases, catalyze transformations that are in some cases difficult to chemically mimick with an equivalent stereo-or regiospecificity and yield. Oxidoreductases are frequently catalyzing reactions that result in the formation of parent ring systems, thereby determining the class of alka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 72 publications
1
45
0
Order By: Relevance
“…S1). A phylogenetic tree based on an alignment of protein sequences corresponding to functionally characterized plant flavoproteins shows high bootstrap support for a monophyletic clade containing BBE homologues from E. californica (36), barberry (B. wilsoniae) (37), and opium poppy (38) (Fig. 2).…”
Section: Isolation Of Fadox Genementioning
confidence: 99%
“…S1). A phylogenetic tree based on an alignment of protein sequences corresponding to functionally characterized plant flavoproteins shows high bootstrap support for a monophyletic clade containing BBE homologues from E. californica (36), barberry (B. wilsoniae) (37), and opium poppy (38) (Fig. 2).…”
Section: Isolation Of Fadox Genementioning
confidence: 99%
“…Each construct encoded the indicated region of BBE fused to either GUS or GFP, and was¯anked by the bbe1 promoter and the nos transcription terminator. N-terminal amino acids of BBE from opium poppy (PsBBE; Facchini et al 1996) are shown aligned to those from Eschscholzia californica (EcBBE; Dittrich and Kutchan 1991) and Berberis stolonifera (BsBBE; Chou and Kutchan 1998). The arrowhead indicates the signal-peptide cleavage site identi®ed in E. californica BBE Forty-eight hours after the bombardment of opium poppy cells with pBBE::GFP, GFP was visible in the nucleoplasm and cytosol of all¯uorescent cells (Fig.…”
Section: A Signal Peptide Targets Bbe To the Ermentioning
confidence: 99%
“…Protein S24 was shown to be homologous to desacetoxyvindoline-4-hydroxylase, an enzyme involved in the biosynthesis of the indole alkaloid vindoline in Catharanthus roseus [55]. Its detection in the latex of P. somniferum raises the question which role this 2-oxoglutaratedependent dioxygenase plays in the isoquinoline alkaloid biosynthesis.…”
Section: Enzymes Involved In Alkaloid Biosynthesismentioning
confidence: 99%